Identification of Stable Reference miRNAs for miRNA Expression Analysis in Adult Neurogenesis Across Mouse and Human Tissues - Daniella Liana Levitis; Julia Si; Kushal Ravishankar; Michal Toborek; Minseon Park (Cells)
Accurate normalization in miRNA studies requires the use of appropriate endogenous controls, which can vary significantly depending on cell types, treatments, and physiological or pathological conditions. This study aimed to identify suitable endogenous miRNA controls for neural progenitor cells (NPCs) and hippocampal tissues, both of which play crucial roles in neurogenesis. Using small RNA sequencing, we identified the most stable miRNAs in primary mouse NPCs and hippocampal tissues and accessed their stability using NormFinder analysis. Six miRNAs—miR-181d-5p, miR-93-5p, miR-103-3p, let-7d-5p, miR-26a-5p, and miR-125a-5p—demonstrated high stability and were evaluated for their suitability as endogenous controls across multiple experimental conditions. All selected miRNAs exhibited consistent expression in the NE-4C mouse cell line but not in ReNcells, a human cell line. For ReNcells, only miR-186-5p, one of the known reference miRNAs tested for comparison, showed stable expression. Notably, miR-103-3p and let-7d-5p were stably expressed in hippocampal tissues from both mouse and human samples but were absent in human brain pericytes, human brain microvascular endothelial cells, and SVG p12 cells, a human fetal glial cell line. This study is the first to identify optimal reference miRNAs for adult neurogenesis in both mouse and human samples, providing reliable options for miRNA normalization and improving the accuracy and reproducibility of miRNA expression analyses in neurogenesis research.